Spontaneously Formed Mott‐Schottky Electrocatalyst for Lithium‐Sulfur Batteries. Issue 22 (28th September 2020) - Wang, Yuankun; Zhang, Ruifang; Sun, Zehui; Wu, Hu; Lu, Shiyao; Wang, Jianan; Yu, Wei; Liu, Jiamei; Gao, Guoxin; Ding, Shujiang
Abstract: Developing effective electrocatalyst and deciphering its mechanism in modulating sulfur‐species‐conversion is still an important but challenging part for lithium sulfur (Li‐S) batteries. Here, a "spontaneous formed" strategy is presented to construct hierarchical CNT@ surface oxidized TiN nanoparticles (CNT@TiON) and the detailed interfaces mediation mechanism of Mott‐Schottky effect is disclosed on Li‐S chemistries. The results indicate the redistribution of local electron density in TiON is critical to enhancing the sulfur‐species utilization, lowering the energy barriers of intermediate step, and facilitating the conversion of PS. As a result, CNT@TiON‐S cathodes deliver significantly improved electrochemical performance, including low polarization, fleet reaction kinetics, and lasting cycle stability. This work embraces the local electronic state at heterojunction interface and paves a new way toward the design and understanding of efficient catalysts for Li‐S batteries. Abstract : This work develops a Mott‐Schottky catalyst using the spontaneous oxidation of TiN in air and highlights the importance of interfacial charge field in Li‐S chemistries. The redistributed electron at heterogenous interface promotes the redox kinetics of polysulfides. Therefore, the CNT@TiON‐S electrodes deliver 1.7‐fold increase in capacity compared to its oxide counterpart.